Exploring the evenness of a group dynamics and communication patterns: A case study of Fadama III additional financing in Osun State, Nigeria - Oladimeji, Folake Victoria; Adereti, Francis Oke; Filusi, Olajide Julius (International Journal of Business Strategy and Social Sciences, 2025)
The study assessed communication and group dynamic patterns in the implementation of Fadama III Additional Financing (AF), specifically identifying and describing group characteristics, analyzing communication and interaction patterns, and determining the strength of group dynamics. A multistage sampling procedure was employed to select respondents for the study. In the first stage, 50 percent of the Local Government Areas (LGAs) were purposively selected from each agricultural zone based on a higher number of participating production groups in the Fadama III AF program, resulting in 6, 4, and 3 LGAs from Osogbo, Iwo, and Ife/Ijesha zones, respectively. The second stage involved selecting 30 percent of the production groups (PGs) in each of the selected LGAs proportionally, totaling 59 PGs. In the third stage, 2 leaders and 2 members from each of the 59 selected PGs were randomly chosen for interviews, totaling 236 respondents. Results indicated that 62.5 percent of the PGs were established for economic purposes, and the majority (84.7%) of PGs had a registered cooperative society under the government. More than half (51.3%) of respondents reported a strong sense of group dynamics. A significant difference was observed in the mean scores of the strength of group dynamics among Fadama III AF beneficiaries across the selected Agricultural Development Projects zones at p≤ 0.05. The study concluded that more than half of the Fadama III AF group beneficiaries exhibited strong group dynamic strength.